IRAP Inhibitors: M1-Aminopeptidase Family Inspiration - Barlow, Nicholas; Thompson, Philip E. (Frontiers in Pharmacology, 2020)
The insulin related aminopeptidase (IRAP) has been proposed as an important therapeutic target for indications including Alzheimer's disease and immune disorders. To date, a number of IRAP inhibitor designs have been investigated but the total number of molecules investigated remains quite small. As a member the M1 aminopeptidase family, IRAP shares numerous structural features with the other M1 aminopeptidases. The study of those enzymes and the development of inhibitors provide key learnings and new approaches and are potential sources of inspiration for future IRAP inhibitors.